EXPERIMENTAL AND COMPUTATIONAL ELUCIDATION OF CORROSION INHIBITION POTENTIAL OF L-HISTIDINE ON MILD STEEL IN AQUEOUS HYDROCHLORIC MEDIUM - Ahmed, Adetoro; Oladunni, Nathaniel; Kolawole, Akiode O.; Lawan, Ishaq Y. (FUDMA Journal of Sciences, 2025)
Deterioration of materials, usually metals, by chemical or electrochemical reactions in relation to their environment has been greatly described by corrosion and inhibitors have been effective in curbing its adverse potential on metals. Experimental and computational elucidation of corrosion inhibition potential of L-histidine in interaction with mild steel in HCl medium has been conducted using weight loss method and quantum chemical calculations. Results obtained revealed that raising the concentration of L-histidine from 0.003 to 0.01 mol dm-3 in aqueous HCl medium, for 2 – 6 hours, inhibits the corrosion progression rate of the coupons. The corrosion rate (CR) was observed to slightly decrease with increase in reaction temperature from 323k to 363k. Decrease in CR (i.e increase in inhibition efficiency) was very significant with the time of contact of the mild steel when the inhibitor was increased from 2hrs to 6 hrs. As the inhibitor’s concentration increases, the inhibition efficiency (IE %), was found to increase. Langmuir adsorption isotherm was used to fit surface coverage values and the significantly high value of the correlation (R2) suggests that Langmuir isotherm perfectly describes the adsorption process. R2 values obtained at 343 k and 363 k temperature is 0.9932 and 0.9921 respectively. The computational elucidation were performed by carry out electronic parameters characterize through quantum chemical calculations which were associated with inhibition efficiency. The electrochemical results are corroborated by theoretical data where E-HOMO and E-LUMO were calculated.
Keywords: Corrosion; Computational; Inhibition; Isotherm; L-histidine; Theoretical; Quantum